A Bantu suite for piano, xylophone, whistles and voices - Hirschland, Heinz (International Library of African Music, 1957)
The three main characteristics of Bantu music are its rhythm, its repetitiveness (fascinating, but also jarring to the white ear) and the downward trend of its scales and melodic motives. For a composer, trained in the European idiom, the problem arises of how to bring this type of African music into a plausible shape without losing its most important features.
Keywords: African Music